Huge renal angiomyolipoma - A. A. Kamalov; N. I. Sorokin; M. A. Khokhlov; A. M. Pshikhachev; A. B. Shomarufov; D. A. Tsigura; Sh. A. Abbosov; A. V. Sitnikov; N. V. Danilova (Вестник урологии, 2023)
Renal angiomyolipoma (AML) is a rare solid benign tumor composed of varying amounts of mature adipose tissue, smooth muscle, and thick-walled vessels. This article presents a clinical observation and immediate results of a two-stage treatment of giant renal AML (preliminary superselective embolization with further partial nephrectomy) in a 58-year-old woman.